ANALYSIS OF THE EFFECT OF AESTHETIC DESIGN AND LABELLING ON PURCHASE INTENTION IN “TLUR” - Y. R. B., Priatmojo; Putri, B. R. T.; Suarta, G. (Jurnal Peternakan Tropika, 2024)
The aim of this research was to analyse the impact of aesthetic design and labelling on consumer buying behaviour of 'tlur' scrub products. Aesthetic design encompasses material, colour, shape, and size, while labelling includes composition, benefits, and usage instructions. The study was conducted between July and September 2023, using primary and secondary sources such as documents, questionnaires, and in-depth interviews. The research sample comprised 42 respondents, consisting of 40 consumers of scrub products, an academic, and a policy maker. The study employed both quantitative and qualitative techniques, and data analysis involved F-test, T-test, Multiple Linear Regression Analysis, and Expert Respondent Analysis. The results showed that aesthetic design and labelling had a positive relationship with purchase intention, with varying degrees of influence depending on the model used